(untitled) (GAIMS Journal of Medical Sciences, 2025)
Introduction: Fractures of the distal humerus are relatively common injuries, distal humerus fractures lead to significant burden on society due to its bimodal distribution with a peak in young males due to high energy trauma (road traffic accidents, fall from height, trauma to arm and gunshot wounds) and a other peak in older females usually by simple falls. There are several methods of fixation available, namely- plate fixation and external fixation. Out of which very commonly performed is plating. Material and Methods: A total of 40 patients distal humerus fractures were treated with dual plating between May 2022 and May 2024. Of these, 20 patients underwent orthogonal plating (Group A), while 20 patients were treated with parallel plating (Group B). Patients were selected based on specific inclusion criteria: age between 18-60 years, fractures of the distal humerus with intra condylar extension, closed fractures, non-compliant patients for conservative treatment, polytrauma patients, and those who refused conservative treatment. Exclusion criteria included patients younger than 18 or older than 60 years, fractures involving the shaft of the humerus, previous humeral surgery, pathological fractures, open fractures, and nerve palsy. This prospective study utilized a sample size of 40 patients, with Group A consisting of odd-numbered patients receiving orthogonal plating and Group B consisting of even-numbered patients receiving parallel plating. Results: Out of 20 operated cases of orthogonal plating, 18 patients had excellent, 2 patients had poor ASES score, whereas in parallel plating group 16 patients had excellent, 2 patients good, 2 patients poor American Shoulder and Elbow Surgeons (ASES) score, no post operative infections were noted, no non-union cases were noted, no significant difference in surgery time, blood loss, mean duration of hospital stay was noted. Conclusion: Both orthogonal plating and parallel plating had similar outcomes with respect to elbow function and early physiotherapy. No significant difference in surgery time, blood loss, mean duration of hospital stay were noted.